Information management of critical knowledge in an IT consulting company - Widoyono, Bambang; Saptono, Ristu; Rohmadi, Arif; Wihidayat, Endar; Syaifuddin, Akhmad; Hendrasuryawan, Brilyan (Universitas Padjadjaran, 2026)
Background: Knowledge Management (KM) plays a crucial role in supporting organizational sustainability, particularly in IT consulting firms where knowledge is predominantly tacit, experience-based, and vulnerable to loss. Many consulting organizations face difficulties identifying which knowledge is truly critical and how to manage it as reusable organizational information. Purpose: This study aimed to identify, prioritize, and manage critical knowledge aligned with organizational strategy at PT XYZ, an IT consulting company. Methods: Using a mixed qualitative–quantitative approach, this study followed six stages: contextual knowledge scoping, tacit knowledge elicitation, knowledge structuring, critical knowledge assessment using Critical Knowledge Factors (CKF), prioritization using Analytical Hierarchy Process (AHP), and repository design for knowledge preservation. Results: The study identified 24 structured knowledge areas, of which 20 were classified as critical. AHP analysis indicated that Gaining Commitment, Reading Opportunities, and Marketing Strategy were the highest priority knowledge assets, primarily embedded in sales and marketing activities. Conclusion: This study demonstrates how tacit knowledge can be transformed into structured organizational information aligned with strategic processes through an information management perspective. Theoretically, this study contributes to information science by conceptualizing critical knowledge as information objects organized through metadata, lifecycle governance, and repository preservation. Implications: In practice, these findings provide the IT consulting firm with a structured approach to safeguarding critical tacit knowledge, reducing reliance on individuals, and strengthening organizational memory. However, the study is limited to a single organizational context, relies on expert judgment, and presents a repository design that remains conceptual rather than technically implemented.